Blunt Instruments, Glass Slippers, and Unicorns: Ocean Governance in a Climate-Changed Gulf of Maine - Farady, Susan (Maine Policy Review, 2023)
Management and governance systems should ideally match the nature of the natural environment and the range of human uses. Today’s ocean and coastal governance system is made up of singular laws and government agencies, the product of years of evolution. This system was never intended to reflect the complexities of the marine ecosystem and varied human uses of marine resources. The resulting “silo-ed” management system has never worked particularly well, but as we face a rapidly changing Gulf of Maine, and accompanying changes in uses, this system’s limitations are increasingly obvious. An “ideal” ocean governance system would be comprehensive and incorporate cumulative impacts of uses on an interconnected ecosystem; decision-making would accurately capture and assess the impacts of all activities upon each other as well as the ecosystem; and decisions would be made in a transparent forum, inclusive of all stakeholders, and overtly assessing the potential trade-offs of any management decision.